PENGARUH PENERAPAN SADARI PADA REMAJA PUTRI TERHADAP KEMAMPUAN DETEKSI DINI KANKER PAYUDARA DI MTS MUHAMMADIYAH PULAU PUNJUNG KABUPATEN DHARMASRAYA - Husna Edi; Sukmawati Sukmawati; Salma Anugra Fitri (PREPOTIF : JURNAL KESEHATAN MASYARAKAT, 2022)
Breast cancer has the highest prevalence in Indonesia, attacking adolescents. This shows that the knowledge and ability of young women is still low about the importance of early detection in order to avoid breast cancer. One way to prevent breast cancer is to do a breast self-examination (BSE). Knowing the effect of implementing breast self-examination (BSE) on the ability of female students in early detection of breast cancer. This type of research is a quantitative study with a research design using Quasi Experimental. The instrument used for the implementation of BSE is a checklist, while for the ability to use an observation sheet. The sampling technique in this study used total sampling with a sample of 10 people. Processing of data using the Statistical Mann Whitenney test. This study shows that all young women can perform BSE 100% while for the ability to detect breast cancer early, almost all of them are able to do early detection of breast cancer. as much as 80% and a small proportion of young women are not able to do early detection of breast cancer 10%. From the results of the study using Mann Whiteney, it was found that P-Value = 1,000 <0.05, meaning that there was no effect of the application of BSE in adolescent girls on the ability to detect breast cancer early. In early detection of breast cancer, it is hoped that the school will always carry out socialization about women's health and cooperate with health workers, especially regarding BSE examinations.